Liposome-encapsulated doxorubicin citrate in previously treated recurrent/metastatic gynecological malignancies. Issue 1 (1st January 2007) - Angioli, R.; Palaia, I.; Calcagno, M.; Manci, N.; Zullo, M. A.; Bellati, F.; Perniola, G.; De Vivo, A.; Benedetti Panici, P.
Abstract : The aim of this study was to evaluate the safety and efficacy of liposome-encapsulated doxorubicin citrate (LEDC) in patients affected by recurrent/metastatic gynecological malignancies scheduled for palliative chemotherapy. Inclusion criteria were proven recurrent/advanced gynecological neoplasms, measurable/assessable disease, adequate organ function, left ventricular ejection fraction >50% as determined by echocardiography, informed consent. LEDC was administered intravenously over 1 h at the dose of either 75 mg/m 2 or 60 mg/m 2 (every 3 weeks until disease progression or toxicity prohibiting further therapy). From May 2003 to September 2005, 36 patients were enrolled. Primary disease was ovarian, endometrial, and cervical cancers in 15 (42%), 11 (30%), and 10 (28%) patients, respectively. LEDC was employed as third- or fourth-line chemotherapy in 25 (70%) and 11 (30%) patients, respectively. The median number of courses of LEDC received was 3 (range 2–9). Six patients (17%) achieved a partial response to treatment lasting 27 weeks and 10 patients (28%) experienced stable disease lasting 18 weeks. The predominant toxicity was hematological, especially neutropenia. Among patients receiving a dose of 75 mg/m 2, two (11%) suspended therapy for febrile neutropenia, and nine (50%) required a dose reduction of 25%. As a result, the next 18 patients were treated at a reduced dose (60 mg/m 2 ) of LEDC. Severe neutropenia (G3–G4) was significantly less common in this group (61% versus 22%; P = 0.04). LEDC has shown antineoplastic activity in previously treated recurrent/metastatic gynecological cancer patients and the toxicity profile could be considered acceptable at a 60 mg/m 2 dosage.